IRPS – An Efficient Test Data Generation Strategy For Pairwise Testing. - Younis, Mohammed I; Zamli, Kamal Zuhairi; Mat Isa, Nor Ashidi (2008)

(untitled)
Software testing is an integral part of software engineering. Lack of testing often leads to disastrous consequences including loss of data, fortunes, and even lives.